2013
DOI: 10.1158/1078-0432.ccr-13-1185
|View full text |Cite
|
Sign up to set email alerts
|

A Dendritic Cell Vaccine Pulsed with Autologous Hypochlorous Acid-Oxidized Ovarian Cancer Lysate Primes Effective Broad Antitumor Immunity: From Bench to Bedside

Abstract: Purpose: Whole tumor lysates are promising antigen sources for dendritic cell (DC) therapy as they contain many relevant immunogenic epitopes to help prevent tumor escape. Two common methods of tumor lysate preparations are freeze-thaw processing and UVB irradiation to induce necrosis and apoptosis, respectively. Hypochlorous acid (HOCl) oxidation is a new method for inducing primary necrosis and enhancing the immunogenicity of tumor cells.Experimental Design: We compared the ability of DCs to engulf three dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
215
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(224 citation statements)
references
References 56 publications
6
215
0
3
Order By: Relevance
“…[11][12][13][14][15][16] The first ever DC-vaccine officially introduced in cancer therapy was sipuleucel-T (Provenge; Dendreon, Seattle, WA), which was approved by the FDA in 2010 for the use in advanced prostate cancer after clinical trials had shown increased survival. 17 Along similar lines many research groups have conducted preclinical studies as well as phase I and II clinical trials to investigate the efficacy and safety of DC-vaccines in GBM and other high grade gliomas.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] The first ever DC-vaccine officially introduced in cancer therapy was sipuleucel-T (Provenge; Dendreon, Seattle, WA), which was approved by the FDA in 2010 for the use in advanced prostate cancer after clinical trials had shown increased survival. 17 Along similar lines many research groups have conducted preclinical studies as well as phase I and II clinical trials to investigate the efficacy and safety of DC-vaccines in GBM and other high grade gliomas.…”
mentioning
confidence: 99%
“…Whole tumor lysate based vaccines also produced more clinical responses than highly specific vaccines. Recently, hypochlorous acid-oxidation has been presented as a new method for preparing tumor lysate and DCs pulsed with hypochlorous acid-oxidized tumor lysate were safe and elicited potent T cell responses against ovarian antigens [22]. DC loading of cancer stem cell lysate is appeared to be more effective than total tumor lysate [23].…”
Section: Antigen Loading Of Dcsmentioning
confidence: 99%
“…PD-L-silenced and antigen mRNA-loaded DCs had improved immunogenic potency as they superiorly boosted ex vivo antigenspecific CD8 + T cell responses from transplanted cancer patients [42]. DCs pulsed with hypochlorous acid-oxidized tumor lysate were found to be safe and two of five vaccinated ovarian cancer patients experienced durable progression-free survival of 2 years and more after DC vaccination [22]. Vaccination of 16 patients with head and neck squamous cell carcinoma with DCs loaded with the tumor peptide p53 was associated with two-year disease free survival of 88% of vaccinated patients [43].…”
Section: Application Of DC Vaccine In Cancer Patients and Its Efficacymentioning
confidence: 99%
“…Anti-cancer vaccination using a whole tumor lysate dendritic-cell (DC) vaccine approach to multiple tumor-associated antigens has proven a useful strategy to elicit or enhance antitumor immune responses, particularly prior to adoptive cell transfer. 7 Our group recently initiated a phase I/II clinical trial in patients with recurrent stage III/IV ovarian cancer using autologous DCs loaded with HOCl-oxidized autologous tumor lysate in combination with anti- angiogenic bevacizumab and low-dose cyclophosphamide. 8,9 Patients in which DC vaccination produced clinical benefit but still presented with evidence of disease following 3 months of therapy were offered to undergo apheresis to collect vaccineprimed peripheral blood T cells.…”
Section: Introductionmentioning
confidence: 99%